2018
DOI: 10.5194/os-14-971-2018
|View full text |Cite
|
Sign up to set email alerts
|

A model perspective on the dynamics of the shadow zone of the eastern tropical North Atlantic – Part 1: the poleward slope currents along West Africa

Abstract: Abstract. The West African seaboard is one of the upwelling sectors that has received the least attention, and in situ observations relevant to its dynamics are particularly scarce. The current system in this sector is not well known and understood, e.g., in terms of seasonal variability, across-shore structure, and forcing processes. This knowledge gap is addressed in two studies that analyze the mean seasonal cycle of an eddy-permitting numerical simulation of the tropical Atlantic. Part 1 is concerned with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 95 publications
0
36
0
Order By: Relevance
“…The magnitude of their poleward transport from that season is thus somewhat larger than the poleward transports during upwelling and relaxation season of 0.7 and 1.8 Sv, respectively, reported here. ROMS by Kounta et al (2018) suggested elevated poleward transports at the eastern boundary during the boreal fall season due to CTWs excited in the Gulf of Guinea, which may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The magnitude of their poleward transport from that season is thus somewhat larger than the poleward transports during upwelling and relaxation season of 0.7 and 1.8 Sv, respectively, reported here. ROMS by Kounta et al (2018) suggested elevated poleward transports at the eastern boundary during the boreal fall season due to CTWs excited in the Gulf of Guinea, which may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 98%
“…Alongshore transport variability at the eastern boundary can be forced locally by variability of Ekman divergence through CTWs (McCreary, 1981;Suginohara, 1982;Wang, 1982) and offshore propagating Rossby waves (e.g., McCreary & Chao, 1985;Suginohara & Kitamura, 1984) or remotely by CTWs propagating into the region from the South (e.g., Kounta et al, 2018). While locally forced barotropic Rossby waves and barotropic and low-vertical mode baroclinic CTWs can establish an alongshore pressure gradient and related poleward flow at the boundary within a few days, geostrophic adjustment by baroclinic Rossby waves requires several months or more.…”
Section: Transport Variability and Wind Stress Curlmentioning
confidence: 99%
See 1 more Smart Citation
“…A discussion is offered in section 4 on the conditions and processes having led to anoxia and on the broader local to regional implications. (Arístegui et al, 2009;Kounta et al, 2018)…”
Section: Citationmentioning
confidence: 99%
“…(a) Thermohaline and flow features of the Northeast tropical Atlantic (Arístegui et al, ; Kounta et al, ) including the Cape Verde frontal zone (CVFZ), North Equatorial Current (NEC), North Equatorial Counter Current (NECC), North Equatorial Undercurrent (NEUC), and West African poleward Boundary Current (WABC). The typical upwelling circulation off southern Senegal is represented in the upper‐right panel: The WABC flows northward and feeds the coastal upwelling with nearly hypoxic subsurface waters.…”
Section: Introductionmentioning
confidence: 99%